2000
DOI: 10.1290/1071-2690(2000)036<0539:vcaioa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Violacein Cytotoxicity and Induction of Apoptosis in V79 Cells

Abstract: Violacein, a pigment produced by Chromobacterium violaceum, is reported to be a potential drug for the treatment of Chagas' disease. Violacein is also effective against leukemia and lymphoma cells in culture (IC50 10(-8) M). Changes in the nuclear acid content, 3-(4,5-dimethylthiazole-2-yl)-2,5-biphenyl tetrazolium bromide reduction and neutral red uptake in these cells were used to evaluate the cytotoxicity of violacein in V79 Chinese hamster (M-8) fibroblasts. Violacein was highly cytotoxic to V79 fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 19 publications
3
44
0
6
Order By: Relevance
“…Preliminary studies had already demonstrated that violacein presents cytotoxicity to V79 fibroblasts (CC 50 = 7 µM; MTT assay) (Melo et al 2000).This cytotoxicity was also verified with the cell lines used in this study, and Violacein showed a concentration-response relationship since the cytotoxicity increased gradually with the increase of its concentration as shown by the tested methodologies ( Figure).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Preliminary studies had already demonstrated that violacein presents cytotoxicity to V79 fibroblasts (CC 50 = 7 µM; MTT assay) (Melo et al 2000).This cytotoxicity was also verified with the cell lines used in this study, and Violacein showed a concentration-response relationship since the cytotoxicity increased gradually with the increase of its concentration as shown by the tested methodologies ( Figure).…”
Section: Resultssupporting
confidence: 81%
“…as an indicator of acute toxic effects in vivo) and are also important for designing more in depth in vitro studies (Eisenbrand et al 2002). These data will be useful for a better understanding of other biological activities attributed to violacein, such as antibacterial, antitumoral and anti-Trypanosoma cruzi activities (Melo et al 2000, Duran & Menck 2001. One strategy used to improve biological activity is the incorporation of active substances into liposomes which offer a substancial improvement in the therapeutic indices of the molecules entrapped in them (Gulati et al 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is a purple pigment that gives tropical bacterium Chromobacterium violaceum its characteristic coloring (1-5). Violacein 5 has potential medical applications as an antibacterial (6 -8), anti-tryptanocidal (8 -10), anti-ulcerogenic (11), and anti-cancer drug (8,(12)(13)(14)(15)(16)(17). The molecule, made of L-tryptophan and molecular oxygen (18 -21), was originally thought to be synthesized by the action of just four enzymes VioABCD (22, 23), but an additional open reading frame (24), also in the operon, was shown to encode the enzyme VioE (25, 26).…”
mentioning
confidence: 99%
“…Esse teste também é importante para verificar a toxicidade de novos compostos nos estágios iniciais de desenvolvimento de fármacos (Putnam et al, 2002), pois o equilíbrio entre os efeitos farmacológicos e toxicológicos de um composto é um requisito essencial para sua aplicabilidade como futuro agente terapêutico (Melo et al, 2002).…”
Section: Resultsunclassified